Associatio between biomarkers in the long-term prognosis of ischemic stroke (Annals of Medical Research, 2021)
Aim: Predicting of the stroke prognosis has utmost importance as the disease has a heavy socioeconomical burden. For this reason, instruments such as stroke severity scales, stroke volume calculations and various biomarkers are used for determination of prognosis. NIHS scale, stroke volume, stroke type, neutrophil/lymphocyte ratio and C-reactive protein levels were reported to be associated with stroke prognosis. In this study we aim to investigate the relationship between these parameters with 8-year-survival from stroke.Materials and Methods: Between January 2010 and January 2012, all patients aged over 18 and diagnosed with arterial stroke were retrospectively investigated. Data regarding survival status were obtained from Death Reporting System (https://obs.gov.tr/) under the surveillance of Ministry of Health. NIHS scale, stroke volume, stroke subtype, neutrophil/lymphocyte ratio and C- reactive protein levels were obtained and compared in deceased and living patients and association between those parameters and survival was sought.Results: Advanced age, male gender, NIHS scale, stroke volume, stroke subtype, neutrophil/lymphocyte ratio were associated with stroke survival. C-reactive protein levels were not be found associated.Conclusion: Our results were consistent with the literature and, NIHS scale, stroke volume, stroke subtype, neutrophil/lymphocyte ratio predicted the stroke prognosis. As there is not enough data present in the literature, our findings were remarkable.